1981
DOI: 10.1037/0012-1649.17.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Parental competence and styles of problem solving/play behavior with children.

Abstract: The relationship of parental psychosocial competence to parent interaction behaviors in a joint problem-solving/play session with children was studied in 23 adult-preschool child pairs. Parents were assessed using self-report questionnaires to determine degrees of self-efficacy, optimistic trust, and an active, planful coping style (i.e., competence). Children and parents participated in a semistructured problem-solving/play task with observers rating the parental behaviors in the interactions; child responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1
3

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(37 citation statements)
references
References 18 publications
3
30
1
3
Order By: Relevance
“…Ego-resiliency has been found to be strongly related to effective functioning in diverse areas of life (Klohnen, 1996), but, to our knowledge, it has not been investigated in relation to quality of parenting. There is only indirect empirical evidence that egoresilient individuals might be better parents; that is, quality of parenting has been found to be empirically related to such parental characteristics as "internal locus of control," "self-esteem," and "ego-strength" (Biringen, 1990;Cox, Owen, Lewis, & Henderson, 1989;Mondell & Tyler, 1981;Stevens, 1988), which are conceptually closely related to the construct of ego-resiliency.…”
Section: Parental Characteristicsmentioning
confidence: 99%
“…Ego-resiliency has been found to be strongly related to effective functioning in diverse areas of life (Klohnen, 1996), but, to our knowledge, it has not been investigated in relation to quality of parenting. There is only indirect empirical evidence that egoresilient individuals might be better parents; that is, quality of parenting has been found to be empirically related to such parental characteristics as "internal locus of control," "self-esteem," and "ego-strength" (Biringen, 1990;Cox, Owen, Lewis, & Henderson, 1989;Mondell & Tyler, 1981;Stevens, 1988), which are conceptually closely related to the construct of ego-resiliency.…”
Section: Parental Characteristicsmentioning
confidence: 99%
“…Dornbusch, Ritter, Leiderman, Roberts, and Fraleigh (1987) recently demonstrated another specific outcome of an authoritative parenting style; they found that adolescents raised by authoritative parents, when compared with adolescents raised by authoritarian parents, have higher levels of academic performance in high school. In a related line of inquiry, Mondell and Tyler (1981) reported significant positive relationships between elements of parental competence and characteristics of parents' teaching interactions with their children, for example, more competent parents treat the child as an "origin," offer more approval and acceptance, and offer more helpful problem-solving questions and strategies.…”
Section: Abstract--grounded Inmentioning
confidence: 99%
“…In accordance with Belsky's (1984) ecological model of the determinants of parenting, parental personality is also one of the most influential predictors of parenting because it affects parental behaviour both directly and indirectly. Although most studies relating personality to quality of parenting have focused on the associations between disturbed psychological functioning and nonoptimal parenting (G. Downey & Coyne, 1990), those few studies that have looked at the role of self-esteem and related concepts such as ego-resiliency in parenting behaviour have also shown strong relationships (e.g., Mondell & Tyler, 1981). It was expected, therefore, that both parental mental health and parental selfesteem would be related to fathers' and mothers' parenting.…”
Section: Introductionmentioning
confidence: 99%